2019
DOI: 10.1016/j.jcyt.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Morphological profiling using machine learning reveals emergent subpopulations of interferon-γ–stimulated mesenchymal stromal cells that predict immunosuppression

Abstract: Background: Although a preponderance of pre-clinical data demonstrates the immunosuppressive potential of mesenchymal stromal cells (MSCs), significant heterogeneity and lack of critical quality attributes (CQAs) based on immunosuppressive capacity likely have contributed to inconsistent clinical outcomes. This heterogeneity exists not only between MSC lots derived from different donors, tissues and manufacturing conditions, but also within a given MSC lot in the form of functional subpopulations. We therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 54 publications
4
76
0
Order By: Relevance
“…Cytoskeletal networks construct cytoplasmic structures and support signal transduction from the extracellular environment to gene expression and chromatin formation in the nucleus . In fact, soluble factors such as cytokines and growth factors affect cellular structure and function . Since monoclonal antibodies against PD‐L1 have been approved for cancer immunotherapy, it is important to investigate effective methods to predict identification of responders using IHC slides .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoskeletal networks construct cytoplasmic structures and support signal transduction from the extracellular environment to gene expression and chromatin formation in the nucleus . In fact, soluble factors such as cytokines and growth factors affect cellular structure and function . Since monoclonal antibodies against PD‐L1 have been approved for cancer immunotherapy, it is important to investigate effective methods to predict identification of responders using IHC slides .…”
Section: Discussionmentioning
confidence: 99%
“…2 In fact, soluble factors such as cytokines and growth factors affect cellular structure and function. 39,40,54 Since monoclonal antibodies against PD-L1 have been approved for cancer immunotherapy, it is important to investigate effective methods to predict identification of responders using IHC slides. 55,56 Interestingly, the levels of PD-L1 expression served to classify tissue morphology in H&E images ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…These studies actively modified cell shape by culturing the cells on a number of micropatterned surfaces, initiating differentiation or stimulating with IFNγ, which all induces morphological changes in the hBM‐MSCs. These changes could either be used to alter the differentiation outcome or predict the BM‐MSC biology . The novelty of the current study lays in the use of naive hBM‐MSC morphology.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that changes in cell shape induced by alternations in the actin cytoskeleton structure determine differentiation outcome of hBM‐MSCs with cellular changes associated with actin de‐polymerization led to enhanced adipocytic differentiation, whereas inhibition of actin de‐polymerization increased osteoblast formation of hBM‐MSCs . Furthermore, one study also shows that stimulation of a immunomodulating pathway can lead to a morphological response in BM‐MSCs . Thus, culturing hBM‐MSCs on biomaterials with specific microstructure or stimulation of certain pathways could be used to obtained clinically relevant cell population with high OB differentiation potential or immunomodulatory properties suitable for clinical transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation